Infratentorial Intracerebral Hemorrhage: Relation of Location to Outcome. Issue 5 (May 2019) - Chen, Ruiqi; Wang, Xia; Anderson, Craig S.; Robinson, Thompson; Lavados, Pablo M.; Lindley, Richard I.; Chalmers, John; Delcourt, Candice
Abstract : Background and Purpose—: Infratentorial intracerebral hemorrhage (ICH) has a poor outcome but is rarely analyzed by cerebellar versus brain stem location. We evaluated this relationship and clinical outcomes among participants of the INTERACT 1 and 2 (Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trials). Methods—: Participants with brain stem and cerebellar ICH were compared. Logistic regression models were used to compare outcomes of death or major disability and quality of life. Results—: Of 195 included patients, 92 (47%) and 103 (53%) had brain stem and cerebellar ICH, respectively. Patients with brain stem ICH were younger (mean [SD] age, 59±13 versus 70±11 years), less female (28.3% versus 50.5%), with higher admission National Institutes of Health Stroke Scale scores (median [interquartile range], 6 [4–10) versus 3 [2–8]), less prior ICH (3% versus 17%), smaller ICH volumes (1.6 mL [1.0–2.8 mL] versus 5.1 mL [2.6–10.7 mL]), and less intraventricular extension (3% versus 39%) than those with cerebellar ICH. Brain stem ICH had higher mortality (odds ratio, 37.1; 95% CI, 1.99–692.27) and worse scores in the European Quality of Life Scale (EQ-5D) pain domain (odds ratio, 3.36; 95% CI, 1.38–8.20). Conclusions—: Cerebellar and brain stem ICH differ in their clinical characteristics and prognosis, with the latter being associated with higher case fatality and worse EQ-5D scores in the pain domain. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifiers: NCT00226096 and NCT00716079.